Revalidation of student evaluation of teaching effectiveness rating scale in Ahmadu Bello University Zaria / Kabiru Jinjiri Ringim...[et al.] - Kabiru, Jinjiri Ringim; Abubakar, Mukhtar Yusuf; Abdullahi, Nasir (Universiti Teknologi MARA, Kedah, 2019)
The growing interest in moving beyond traditional measures of teachers' performance and effectiveness in the classroom as the basis for making decisions for promotion and selection for leadership roles in Ahmadu Bello University (ABU), Zaria led to the adoption of Student Evaluation of Teaching Effectiveness Rating Scale (SETERS). Therefore, the objectives of this study were to determine the suitability and validity of SETERS adoption in the Business Administration Department, Ahmadu Bello University, Zaria, Nigeria. The study used descriptive research design. A proportionate stratified random sampling technique was used for a sample selection of the respondent from undergraduate students of semester one (1) to semester eight (8) respectively. Eight hundred (800) questionnaires were returned out of the 1,000 questionnaires distributed by hand delivery to the students with the help of four Research Assistants. The data collected was processed using SPSS for descriptive and inferential analysis. Results emanating from principal component analysis suggested five factors: 1) Clear delivery of course information; 2) Knowledge and Experience sharing; 3) Clear course outline and direction; 4) Lecturer Interaction and Student participation; 5) Provision of progress report to the student, the most important. The components revealed an Eigenvalue greater than one explaining the variance respectively and accounted for 65.46% of the total scale variance. The correlation matrix showed the presence of many significant coefficients of 0.3 and above. The Kaiser-Meyer-Olkin value reached statistical significance, supporting the factorability of the correlation matrix. In an attempt to establish construct validity, convergent validity was examined using Average Variance Extracted (AVE) that shows how indicators of SETERS construct converged and share common variance. Finally, reliability test for each dimension of SETERS emerged with a Cronbach's alpha ranges from 0.692 to 0.826 and a composite reliability coefficient of 0.907 for the major variables in the questionnaire used for the study implied that the instrument was reliable. Hence the instrument had excellent reliability concerning the internal consistency. The outcomes also confirmed SETERS as demonstrating strong convergent validity. It was concluded that SETTERS in its present form (i.e., in this study) is suitable for use in the evaluation of teaching effectiveness of lecturers in Ahmadu Bello University, Zaria Nigeria.